2002
DOI: 10.1088/0953-2048/15/5/331
|View full text |Cite
|
Sign up to set email alerts
|

Application of electron backscatter diffraction to bulk high-Tc superconductors

Abstract: We have successfully obtained electron backscatter diffraction (EBSD) Kikuchi patterns on various bulk high-Tc superconductors (polycrystalline KClO3-doped and undoped YBa2Cu3O7−δ (YBCO), single crystalline YBCO and NdBa2Cu3O7−y) and on YBCO and NdBCO thin films. We have established a sample polishing procedure to obtain intense Kikuchi patterns without an additional carbon coating of the ceramic superconductors. We present Kikuchi patterns, pole figures and orientation maps of the samples. On the polycrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 17 publications
4
35
0
Order By: Relevance
“…The secondary peak is only seen at small fields, below the second step in the transition curves the presence of a secondary phase, it might be possible to prepare pure samples by further improving the processing conditions. This also implies that conclusions concerning the vortex phase diagram [3] have to be reconsidered carefully; especially the origin of the secondary peak might not be an indication of a phase transition in the vortex lattice, but might be due to the presence of a weaker superconducting phase; hence the origin of the secondary peak effect might be of the same type as in the superconductors with the 123-structure [9]. To conclude, we have found that FCC and ZFC-W curves of Bi-based superconductors show a second step in the superconducting transition in fields above 4 T. This second step is directly linked to the secondary peak effect, and to the steep increase of j c at temperatures below 20 K, as observed in all Bi-based superconductors.…”
Section: R3mentioning
confidence: 99%
“…The secondary peak is only seen at small fields, below the second step in the transition curves the presence of a secondary phase, it might be possible to prepare pure samples by further improving the processing conditions. This also implies that conclusions concerning the vortex phase diagram [3] have to be reconsidered carefully; especially the origin of the secondary peak might not be an indication of a phase transition in the vortex lattice, but might be due to the presence of a weaker superconducting phase; hence the origin of the secondary peak effect might be of the same type as in the superconductors with the 123-structure [9]. To conclude, we have found that FCC and ZFC-W curves of Bi-based superconductors show a second step in the superconducting transition in fields above 4 T. This second step is directly linked to the secondary peak effect, and to the steep increase of j c at temperatures below 20 K, as observed in all Bi-based superconductors.…”
Section: R3mentioning
confidence: 99%
“…Based on the analysis of the recorded CI value, a multiphase analysis is realized. A detailed description of the measurement procedure can be found in [10] and [11]. The results of the EBSD measurement are presented in form of maps, the most important thereof are the so- were performed for each sample twice; one with a step size of 1 m as overview and a detail scan with a step size of 50 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The surfaces were subsequently dry-polished using 3M polishing papers as described in Ref. [7], using only ethanol for cleaning purposes. This procedure yields high image quality Kikuchi patterns and has been demonstrated to work well even on various polycrystalline YBCO samples [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the measurement procedure can be found in Refs. [7,8]. Figure 1 gives the SEM/EDX-analysis of the YBCO sample with 0.8wt.-% DU addition.…”
Section: Methodsmentioning
confidence: 99%